Problems in using agricultural information from television among farmers in Malaysia - Ramli, Nor Sabila; Hassan, Md. Salleh; Abu Samah, Bahaman; Shahkat Ali, Muhamad Sham; Mohamed Shaffril, Hayrol Azril; Azaharian, Zoheir Sabagpour (Canadian Center of Science and Education, 2013)
Agriculture today must meet the demands of modernization, which include creating productive and innovative products. The success of this sector is aided by the evolution of technologies such as Information Communication Technology (ICT). Though television is categorized as traditional media, it is still considered an essential component of ICT and has been proven to play a crucial role in agricultural development, particularly on its extension process. This paper focuses on the problems faced by the agriculture community in receiving relevant information through television. This is a quantitative study which uses a questionnaire to obtain the data needed. A total of 400 respondents among farmers from four selected states in Peninsular Malaysia were surveyed. The data reveals that the main problems faced are few opportunities to watch television, short air times, and the fact that agriculture programs are not the farmers’ main preference in terms of what to watch. Based on the results, a related discussion is conducted and recommendations highlighted; these can assist concerned parties in strengthening their extension strategies.